The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1006/dbio.1996.0039
|View full text |Cite
|
Sign up to set email alerts
|

Defective Chorioallantoic Fusion in Mid-gestation Lethality of Parthenogenone ⇔ Tetraploid Chimeras

Abstract: Previous studies of parthenogenetic embryos revealed severe perturbations of both embryonic and extraembryonic tissue lineages during postimplantation development. The majority of pure parthenogenetic concepti have no recognizable axis and exhibit preferential terminal differentiation of their trophectoderm and primitive endoderm. To further define the role of the extraembryonic lineages in parthenogenetic development, we provided them with zygote-derived extraembryonic tissues by aggregating them with fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Sperm quality is often associated with the embryo's ability to progress to implantation. Paternally expressed genes modulate the proliferation and invasiveness of trophoblast cells and subsequent placental proliferation (29,30). Furthermore, evidence suggests that abnormalities in sperm DNA may affect embryo development and possibly increase the risk of miscarriage (31).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm quality is often associated with the embryo's ability to progress to implantation. Paternally expressed genes modulate the proliferation and invasiveness of trophoblast cells and subsequent placental proliferation (29,30). Furthermore, evidence suggests that abnormalities in sperm DNA may affect embryo development and possibly increase the risk of miscarriage (31).…”
Section: Discussionmentioning
confidence: 99%
“…2E) and frequently included a balloon-like structure protruding from the caudal end of the embryo, probably the allantois (Fig. 2E) (Spindle et al 1996). A subset of the E8.5 mutant embryos had developed further, and specific tissues and structures could be identified.…”
Section: Female Embryonic Lethalitymentioning
confidence: 98%
“…In the chimera method, parthenogenetic embryos or pES cells were aggregated with fertilised tetraploid embryos to introduce a normal placenta derived from a wild-type embryo and most of them failed to develop to full term (Barton et al, 1985;Chen et al, 2009;Spindle et al, 1996;Thomson and Solter, 1988). Therefore, it was concluded that differences in cell origin between foetus and placenta could not support foetal development effectively.…”
Section: Discussionmentioning
confidence: 99%